2007
DOI: 10.1027/0227-5910.28.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Suicide in Prisons, Part II

Abstract: Abstract. The International Association for Suicide Prevention created a Task Force on Suicide in Prisons to better disseminate the information in this domain. One of its objectives was to summarize suicide-prevention activities in the prison systems. This study of the Task Force uncovered many differences between countries, although mental health professionals remain central in all suicide prevention activities. Inmate peer-support and correctional officers also play critical roles in suicide prevention but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…In Australia, one study found that the rate of suicide is five and 12 times higher among incarcerated men and women, respectively, compared with the general population (Kariminia et al 2007). While several countries have developed targeted prevention strategies, the epidemiology of suicide in prison suggests that current strategies are inadequate and must be improved to meet the complex needs of incarcerated adults (Daigle et al 2007; Marzano et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In Australia, one study found that the rate of suicide is five and 12 times higher among incarcerated men and women, respectively, compared with the general population (Kariminia et al 2007). While several countries have developed targeted prevention strategies, the epidemiology of suicide in prison suggests that current strategies are inadequate and must be improved to meet the complex needs of incarcerated adults (Daigle et al 2007; Marzano et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A 2002 survey estimated that seven percent of prisoners played peer support roles [ 19 ]. Justifications include: ability of peers to connect with other prisoners [ 20 ] and to have social influence with vulnerable populations resistant to professional advice [ 21 , 22 ]; direct benefits for the peer deliverers themselves [ 20 , 23 ]; wider benefits for the prison system including effective use of resources [ 24 , 25 ]; expanding the range of health services in the criminal justice system [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…One literature review of prison-based peer education schemes noted the dearth of evidence demonstrating effectiveness, despite positive impacts reported by some studies [ 22 ], while a recent systematic review of peer health promotion concluded that peer education could impact positively on attitudes, knowledge and behaviours of sexual health and HIV prevention, but there was little research on other health issues [ 31 ]. Studies of peer support for suicide prevention/self-harm [ 20 , 24 ] report benefits of peer-delivered emotional support, such as decreased prevalence of suicide [ 36 , 37 ]. Peer-based interventions might be more cost-effective than professionally-delivered ones [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Relative to age-adjusted rates in the general population, suicide rates in male prisoners are five times higher in England and Wales, 6 and large proportionate excesses have been found in the USA 7 and some mainland European countries. 8 Potentially modifiable factors have been the focus of suicide prevention guidelines in prisons, 9,10 although there has been little attention to specific psychiatric disorders. A recent systematic review showed that clinical factors have strong associations with suicide in prison, but which diagnoses and their relative contributions were uncertain.…”
mentioning
confidence: 99%